Tesis previa a la obtencion del grado de magister en seguridad industrial mención prevención de Riesgos y Salud Ocupacional. - Tacuri Yungan, Fabián Bolívar (2017)
The present research work has been carried out to demonstrate that the elaboration and application of the "Occupational Health and Safety System" reduces the risks in the development of the LYREC CIA COMPANY activities. LTDA, from the city of Riobamba. All employers in both the public and private sectors must implement the Occupational Health and Risk Prevention System. According to the classification of the Ministry of Labor, regarding the categorization of risk by sectors and productive activities, it indicates that the companies that provide maintenance services and construction of electric networks are located in category 9, therefore it is a high risk company. THE COMPANY LYREC CIA. LTDA, aims to provide technical services in all branches of the electricity area. The management of a company in the field of occupational health and safety can be achieved through the implementation of the Occupational Health and Safety System because Regulation 957 and Decision 584 (Andean Instrument for Safety and Health at Work), determined that "The risks of work is the responsibility of the employer" and that there are obligations, rights and duties to be fulfilled in relation to the prevention of existing risks in companies. For which a study of occupational risks was carried out, obtaining that the risks present in the company are: physical, mechanical, psychosocial chemical risks, ergonomic risks and major accidents. The determination of risks was made through an analysis of the activities during the work process, through checklists, inspections. The risk measurement was carried out in all activities immersed in the work, using tools that allowed us to estimate them. Subsequently, the mechanical risks assessment was carried out using the INSHT method (National Institute for Safety and Hygiene at Work), the Rula method for ergonomic risks and finally the implementation of the Occupational Health and Safety System was implemented. same that is in accordance with current regulations.